The mutation in splicing factor genes correlates with unfavorable prognosis, genomic instability, anti-tumor immunosuppression and increased immunotherapy response in pan-cancer - Luo, Jiangti; Chen, Canping; Liu, Zhixian; Wang, Xiaosheng (Frontiers in Cell and Developmental Biology, 2023)
Splicing abnormality resulting from somatic mutations in key splicing factor genes (SFG) has been detected in various cancers. Hence, an in-depth study of SFG mutations' impact on pan-cancer is meaningful. This study investigated associations of SFG mutations with clinical features, tumor progression phenotypes, genomic integrity, anti-tumor immune responses, and immunotherapy response in 12 common cancer types from the TCGA database. Compared to SFG-wildtype cancers, SFG-mutated cancers displayed worse survival prognosis, higher tumor mutation burden and aneuploidy levels, higher expression of immunosuppressive signatures, and higher levels of tumor stemness, proliferation potential, and intratumor heterogeneity (ITH). However, SFG-mutated cancers showed higher response rates to immune checkpoint inhibitors than SFG-wildtype cancers in 6 cancer cohorts. Single-cell data analysis confirmed that SFG mutations were associated with increased tumor stemness, proliferation capacity, PD-L1 expression, ITH, and aneuploidy levels. Our data suggest that the mutation in key splicing factor genes correlates with unfavorable clinical outcomes and disease progression, genomic instability, anti-tumor immunosuppression, and increased immunotherapy response in pan-cancer. Thus, the SFG mutation is an adverse prognostic factor and a positive marker for immunotherapy response in cancer.